Leveraging technology for value creation in the context of smart sustainable cities: five potential approaches i financial technology (fintech) - Kramer, Isabel (2022)
This master thesis report investigates the potential of five different innovations for value creation in the context of Smart Sustainable Cities by 2050,applyingthe research question “How to create value by entrepreneurially using innovations in Smart Sustainable Cities?”. Primary(interviews with experts)and secondary research was conducted. In-depth analyses and assessments of value creation and sustainability; critical examinations of the five innovations' challenges, interconnections, and potential are performed, concluding that by applying disruptive technology that surpass the requirements of the Smart City Canvas, leverage environmental sustainability without sacrificing price, quality or other advantages, value creation is ensured.